Seroprevalence of anti-SARS-CoV-2 antibodies and risk factors among healthy blood donors in Luanda, Angola - Cruz S. Sebastião (BMC, 2021)
Abstract Background SARS-CoV-2 emerged in China and spread throughout the world due to its rapid transmission. The exposure rate in the healthy population is unknown, mainly in resource-limited countries. Herein, we estimated the seroprevalence of anti-SARS-CoV-2 antibodies and risk factors among blood donors in Luanda, the capital city of Angola. Methods This was a retrospective study conducted with 343 blood donors. Chi-square and logistic regression were calculated to predict the independent variable for SARS-CoV-2 infection and deemed significant when p < 0.05. Results Seroprevalence of anti-SARS-CoV-2 was 4.7%. Positivity rates varied to age groups (3.5–14.3%), gender (0–5%), area of residence (3.1–.6%), educational level (5.1–10.2%), occupation (4.4–7.7%), and the blood donor category (2.0–5.1%). Past and recent infections were detected in 3.2% and 1.5%, respectively. Blood donors under the age of 20 years (OR: 4.58, p = 0.241) and from non-urbanized areas (OR: 1.86, p = 0.293) presented a high risk related to infection. The infection was higher in blood group A and lower in blood group O. The risk of SARS-CoV-2 infection has increased from January 2020 (OR: 0.03, p = 0.001) to August 2020 (OR: 0.57, p = 0.426). Conclusions We provide an estimate of the exposure of healthy blood donors in Luanda. Also, we detected anti-SARS-CoV-2 in January 2020, indicating that the SARS-CoV-2 could have been imported during the first month of 2020. Further studies should be performed to assess the exposure rate in different groups from Angola.